A qualitive reasoning approach for improving query results for sketch based queries by topological analysis of spatial aggregation - Chipofya, Malumbo Chaka (2010)
Dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science in Geospatial Technologies.